2004
DOI: 10.1002/ajmg.a.30110
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular variability of the holoprosencephalic spectrum

Abstract: Since 1996, a European network has been organized from Rennes, France and holoprosencephalic files were collected for clinical and molecular study. Familial instances of typical and atypical holoprosencephaly (HPE) were found in 30% of cases. All affected children had psychomotor delay with microcephaly, often associated with endocrine, digestive, and respiratory abnormalities, and thermal dysregulation. Among 173 subjects in the molecular study, 28 heterozygous mutations were identified (16%): 15 SHH mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 21 publications
(15 reference statements)
4
77
0
1
Order By: Relevance
“…As SMMCI, CNPAS has long been reported as a mild form of holoprosencephaly (5-9). The association of holoprosencephaly with a wide variety of craniofacial and extracranial anomalies is well recognized and individuals with holoprosencephaly have been ascribed to a variety of syndromes with multiple congenital anomaly (27,28). Our study showed that extracranial anomalies also frequently occurred in patients with CNPAS.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As SMMCI, CNPAS has long been reported as a mild form of holoprosencephaly (5-9). The association of holoprosencephaly with a wide variety of craniofacial and extracranial anomalies is well recognized and individuals with holoprosencephaly have been ascribed to a variety of syndromes with multiple congenital anomaly (27,28). Our study showed that extracranial anomalies also frequently occurred in patients with CNPAS.…”
Section: Discussionsupporting
confidence: 54%
“…Half of the mutations have been found in the SHH gene, which is known to play a critical role in early forebrain and CNS development. However, as no anomaly to these genes were found in 80% of holoprosencephaly cases, other genes are likely to be involved (27,31). As reported in …”
Section: Discussionmentioning
confidence: 66%
“…15 In a retrospective survey of 104 living children with HPE, Stashinko et al 16 found that 51% were microcephalic at birth. Mutations in SHH have been found in some patients with microcephaly but without HPE.…”
Section: Discussionmentioning
confidence: 99%
“…Such disruptions could result in the subtle alterations in interneurons that are implicated in a variety of cortical illnesses. Indeed, although loss-of-function mutations in SHH in humans can result in severe holoprosencephalies, more subtle mutations or variable penetrance can result in a spectrum of disorders that includes abnormalities of learning and attention, and seizures (Muenke and Beachy, 2000;Heussler et al, 2002;Lazaro et al, 2004;Nieuwenhuis and Hui, 2005).…”
Section: Alterations In Shh-responsive Gene Expression Correlate Withmentioning
confidence: 99%